ANALYSIS OF EMPLOYEE SATISFACTION TOWARDS WORK MOTIVATION AND ITS IMPLICATIONS ON THE QUALITY OF HEALTH SERVICES (SURVEY STUDY AT IBU ANAK CAHAYA SANGATTA HOSPITAL KALIMANTAN TIMUR) - Maindoka, Regina Tirza; Yuliaty, Farida; Rasyid, Renaldi Prasetya Nagar; Paramarta, Vip; Nugroho, Taufan (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2026)
Human resources are crucial and inseparable from any organization, whether it be an institution or a hospital. Human resources are also key to determining the development of service quality, as assessed by performance. This study aims to analyze employee satisfaction, work motivation, and the quality of healthcare services at Cahaya Sangatta Maternity and Child Hospital, East Kalimantan. This study used a quantitative approach. The sample size consisted of 56 respondents. Data analysis used descriptive analysis and verification analysis using path analysis. The results of the descriptive analysis of employee satisfaction, work motivation, and healthcare service quality indicated good ratings from respondents, although several areas needed to be improved. Meanwhile, the verification study, based on the path analysis model, showed positive path coefficients between variables, and the indirect effect path coefficient was greater than the direct effect (66.3% > 53.9%), indicating that work motivation, as an intervening variable, is able to mediate employee satisfaction and healthcare service quality.